Joyful Learning Using Quizzis to Increase Learning Interest Post Covid-19 - Niken Dwi Setyaningsih; Dian Permatasari Kusuma Dayu (Jurnal Basicedu, 2022)
Limited face-to-face learning which only focuses on giving assignments has an impact on the low interest of students in participating in the teaching and learning process in class. One solution that can be applied is to apply a quizziz-based joyful learning model that can foster student interest in learning. This study aims to increase students' interest in learning by applying a quizziz-based joyful learning model in limited face-to-face learning. This research is a classroom action research with a subject of 10 students. Data were collected by means of observation, documentation, tests and questionnaires. Data were analyzed using qualitative descriptive analysis techniques. The results showed an increase in students' interest in learning in pre-action 41%, cycle I by 63.8% and cycle II by 84.3%, categorized as very strong. Thus, it can be concluded that the application of the quizziz-based joyful learning model can be used as an alternative solution in learning because it can increase students' interest in learning.